EFFECTS OF LAND AREA AND AGRICULTURAL INVESTMENT ON LABOR THROUGH GRDP DISTRICT / CITY OF EAST JAVA 2017 - Achmad Daengs GS; Mahjudin Mahjudin; Eva Desembrianita (Optimum: Jurnal Ekonomi dan Pembangunan, 2020)
The objectives of this study are to probe Â the effects of land area and agricultural investment on labor through district / city GRDP in East Java. This research uses explanatory type by a quantitative approach. Data collection techniques in this study are carried out by means of a literature study. Data analysis technique used is Structural Equation Model (SEM) with the Smart Partial Least Square (PLS) tool. The results in this study indicate that: (1) Land Area has a significant effect on district / city GRDP of East Java; (2) Agricultural Investment has a significant effect on district / city GRDP of East Java; (3) GRDP has a significant effect on District / City labors of East Java.Â